(untitled) (Perner’s Contacts, 2014)
The article is devoted to the analysis of the road capacity through the town Přerov. The program ArcGIS Network Analyst is used for performing the analysis. The results, gained by using this program, were compared with the real figures of the road capacity at the selected routes. The aim is to find the real road capacity through the town Přerov and assess the condition of road transport and get a tool for assessment of various suggested modifications of traffic system ready.